2017
DOI: 10.1155/2017/6160785
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides fromTrichosanthes Fructusvia Ultrasound-Assisted Enzymatic Extraction Using Response Surface Methodology

Abstract: An efficient procedure for ultrasound-assisted enzymatic extraction of crude polysaccharides from Trichosanthes Fructus (crude TFP) using response surface methodology (RSM) was developed. The Box–Behnken design was applied to optimize the effects of pH (X1), enzyme amount (X2), extraction temperature (X3), and liquid-to-solid ratio (X4) on the extraction. The statistical analysis indicated that the independent variables (X4, X2, and X3), the quadratic coefficients (X12, X22, X32, and X42), and the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Chen et al. (2017) successfully reported the polysacchardies from Trichosanthes Fructus using UAE and optimized the extraction parameters using RSM for maximum yield of polysaccharides. Polysaccharides were extracted by ultrasound‐assisted method from hazelnut skin and tobacco leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al. (2017) successfully reported the polysacchardies from Trichosanthes Fructus using UAE and optimized the extraction parameters using RSM for maximum yield of polysaccharides. Polysaccharides were extracted by ultrasound‐assisted method from hazelnut skin and tobacco leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that EGLP exhibits better antitumor effect than the original polysaccharide, implying the potential of EGLP in improving quality of life of the organism as well as inhibiting tumor growth, which was in accordance withthe previous research indicating that the enzymatic extraction of crude polysaccharide from Trichosanthes fructus exerts higher antitumor activity than the native polysaccharide. 8…”
Section: Discussionmentioning
confidence: 99%
“…ultrasound irradiation, 50°C, 100 W, 60% duty cycle, and solid to solvent ratio of 0.3:20) [28]. Polysaccharides from T. fructus were obtained using UAE by optimizing several independent variables and their interactions via response surface methodology [29]. Researchers have extracted polyphenols, flavonoids, polysaccharides and anthocyanins from different crop varieties like mulberry, blackcurrant, peanut shells, etc.…”
Section: Cactusmentioning
confidence: 99%